Development, Pilot, and Evaluation of a Qualitative Documentation Tool for Pharmacists to Share High Impact Patient Intervention Stories - Alex William Middendorf; Aaron Hunt; Alexa Vanden Hull; Deidra Van Gilder; Erin Miller; Sharrel Pinto (University of Minnesota Libraries Publishing, 2024)
Background: Community pharmacists are often the most accessible member of the healthcare team to many patients and play a key role in managing their chronic conditions, such as diabetes or heart disease, through expanded pharmacy services like Medication Therapy Management. Despite their accessibility, pharmacy services are often underutilized due, in part, to a lack of adequate reimbursement models for pharmacy services. There is a need for qualitative data to be collected to indicate the full impact of those services and why they are so important in a patient's healthcare journey. Methods: An online Patient Stories Reporting Tool (PRST) was developed to allow outpatient pharmacists to document their perspectives of select direct patient care encounters that they felt showcased their value. In a pilot test, the PSRT was distributed to pharmacists from a partnering pharmacy organization. Qualitative data was collected, assessed by project team members, and organized by intervention types. For select stories, the otherwise undocumented nuances of delivered services and their impact were considered. Results: Forty-seven stories were reported by 17 pharmacists across 13 practice sites from August 2021 to March 2023. Three types of key interventions delivered were identified including General Patient Education (7 stories), Medication Optimization (20 stories), and Cost Reduction (20 stories). Given the nature and scope of this initial pilot, one story for each of the three most prevalent intervention types was identified as exemplifying the types of stories the tool can collect. Conclusions: The three selected stories help to characterize the services pharmacists provide, the important nuances of pharmacist-patient interactions, and the value of sharing these stories through tools like the PSRT. Through these stories, the PSRT also begins to record the nuances of pharmacist interventions and the impact they can make in a patient's healthcare journey. Potential applications of the tool are multivarious including leading to improvements in the perception of pharmacists' roles on the healthcare team and justifying reimbursement models.